Is it art or science? Chef’s competencies for success - Zopiatis, Anastasios (My University, 2010)
One of the most challenging professions in the hospitality industry, comprised of both scientific mastery and artistic innovation, is the Chef. It is imperative that these positions are occupied by individuals who possess the appropriate set of skills allowing them to perform with equal success in both culinary, as well as managerial competence. Thus, this research sets out to investigate, from “the Chef's” perspective, competencies required for a successful career in the field as well as the level to which these competencies have been developed (acquired) on-the-job. A self-administered questionnaire consisting of 27 competency items was administered to Chef professionals working in Cyprus. The findings revealed that technical (culinary-specific) competencies were considered as most important, followed by leadership-management competencies. In contrast, conceptual (creative-adaptive) competencies were ranked low by the respondents. In addition, numerous significant differences were revealed based on demographics and other industry-related factors.
Keywords: Chefs; Competencies; Cyprus hospitality industry; Training needs